Neonatal Fc receptor mRNA expression in gastrointestinal tissues from pigs fed meal or pelleted diets with or without irradiated and non-irradiated spray-dried animal plasma - C N Groesbeck; T E Burkey; J Ernest Minton; Michael D Tokach; Joel M DeRouchey; Robert D Goodband; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2007)
The neonatal Fc receptor (FcRn) participates in intracellular trafficking of IgG and the maintenance of circulating IgG. The relationship between the FcRn and IgG may also augment host defense immunosurveillance. The current studies evaluated FcRn mRNA from intestinal tissues in fetal pigs and FcRn mRNA in weaned pigs fed meal or pelleted diets with or without irradiated or non-irradiated spray-dried animal plasma. In Exp. 1, fetal pigs were obtained at d 55 and 70 of gestation (n = 5 fetuses/gestational age) and total RNA was isolated from intestinal tissues for quantitative real-time PCR (qPCR) to determine mRNA for FcRn. The FcRn transcripts were observed in all samples, and greater levels of FcRn mRNA were observed in d 55 fetuses compared to d 70 fetuses. In Exp. 2, weaned pigs were used in an 11-d growth assay to determine the effects of feeding meal and pelleted diets with irradiated or non-irradiated spray-dried animal plasma (AP 920) on FcRn expression in intestinal tissues. Pigs were blocked by weight and randomly allotted in a 2 × 2 factorial to one of four dietary treatments. Main effects were diet form (meal or pellet) and either irradiated or non-irradiated spray-dried animal plasma. Jejunal, ileal, and cecal tissues were collected from 24 pigs at the conclusion of the growth assay. Total RNA was isolated to quantify relative mRNA expression of FcRn. The FcRn mRNA transcripts were observed in all tissues. The FcRn mRNA was more abundant (P<0.02) in pigs fed the non-irradiated plasma compared with the pigs fed irradiated plasma. The FcRn mRNA was more abundant (P<0.05) in pigs fed the meal diets compared with the pigs fed pelleted diets. In conclusion, these data suggest that fetal and weanling pig tissues have FcRn mRNA present in the jejunal, ileal, and cecal sections of the small intestine. These data also indicate that FcRn varies with age in pigs. Diet form (meal or pellet) and irradiation of spray-dried animal plasma affects the expression of FcRn in weanling pigs.; Swine Day, 2007, Kansas State University, Manhattan, KS, 2007
Keywords: Kansas Agricultural Experiment Station contribution; no. 08-121-S; Swine day; 2007; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 985; Swine; Feed manufacturing; Fc receptor; Gestation